Association between hamstring flexibility and sprint speed after 8 weeks of yoga in male rugby players - Tilak Raj; Michael J Hamlin; Catherine A Elliot (International Journal of Yoga, 2021)
Background: A Yoga-asana-based intervention has demonstrated its ability to improve flexibility of individuals, but has not been explored in rugby players. We hypothesized that a structured yoga intervention may have an effect on flexibility and sprint performance in male rugby union players. Methods: It was a controlled trial research design and players were assigned using random sampling to one of the two groups; a yoga group (n = 16) that practised yoga for 1 h 2 times a week for 8 weeks in addition to their normal rugby training and a control group (n = 15) with regular rugby training but no yoga intervention. Yoga intervention included 32 yoga postures to address both the upper and lower extremities of the body. Data were collected during preseason and mid-season on hamstring flexibility (sit and reach test), and sprint performance (measured at 5, 10, and 30 m). Results: One hundred and twenty participants were screened and thirty-one players volunteered for the study. Interactions between groups and differences between pre- and post-intervention scores were analyzed using analysis of variance using SPSS (version 24.0). Significance was set at an alpha level of P = 0.05. The yoga group showed a small nonsignificant decrease (-1.2% ± 21.4%, P = 0.05) in hamstring flexibility compared to the control group which demonstrated a large significant decrease (-14.8% ± 23.7%) (mean % change ± 95% confidence interval [CI], P < 0.05). The yoga group also showed minor nonsignificant improvements in sprint times -3.2% ± 10.4%, -0.7% ± 9.0% for the 5 and 10 m sprints, respectively, (mean % change ± 95% CI) compared to controls -0.4% ± 10.2%, 0.4% ± 7.9%. Conclusions: Findings suggest that completing a structured yoga intervention alongside normal rugby training during the rugby season, yoga helped rugby players maintain their hamstring flexibility but did little to improve sprint performance during the season.